2008
DOI: 10.1097/coc.0b013e31805c142f
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Capecitabine and Oxaliplatin in Combination With the Proteasome Inhibitor Bortezomib in Patients With Advanced Solid Tumors

Abstract: Weekly bortezomib can be safely combined with full doses of capecitabine and oxaliplatin. As 1.6 mg/m(2) weekly of bortezomib is the maximum tolerated dose in single-agent studies, no further dose escalation was performed in this study. Preliminary evidence of antitumor activity is demonstrated. The further evaluation of this combination in diseases for which capecitabine and oxaliplatin have efficacy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…It has been hypothesized that pre-existing subclinical, myeloma-related peripheral nerve damage may exist as a concurrent event responsible for the high incidence of CIPN in this specific population of cancer patients. This possibility is supported by the observation that the incidence of clinically relevant CIPN is lower in clinical trials with bortezomib in the treatment of solid tumors than in the treatment of hematologic malignancies [11].…”
Section: Epidemiologymentioning
confidence: 97%
“…It has been hypothesized that pre-existing subclinical, myeloma-related peripheral nerve damage may exist as a concurrent event responsible for the high incidence of CIPN in this specific population of cancer patients. This possibility is supported by the observation that the incidence of clinically relevant CIPN is lower in clinical trials with bortezomib in the treatment of solid tumors than in the treatment of hematologic malignancies [11].…”
Section: Epidemiologymentioning
confidence: 97%
“…Few studies in that regard have been performed, but uncontrolled trials suggest no increase in the incidence of severe peripheral neuropathy when oxaliplatin is associated with vinca alkaloids 32 , taxanes 33 , and proteasome inhibitors 34 .…”
Section: The Peripheral Nervesmentioning
confidence: 99%
“…First, many authors have shown a better antitumor activity, in terms of a higher reduction in tumor growth without significantly increasing toxicity, exerted by bortezomib when used in combination with other chemotherapeutic agents in different preclinical studies. Based on these findings, to date various clinical trials are ongoing in different hematologic and solid tumors (3,(18)(19)(20). Second, fenretinide, unlike other retinoids, is well tolerated in humans, but it is only partially efficacious due to both a scanty oral delivery and a rapid metabolism (21).…”
mentioning
confidence: 99%